The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.otsr.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of the normal Japanese glenoid and comparison with the normal French glenoid

Abstract: IV: retrospective or historical series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In an evaluation of 140 shoulders of patients who were a mean age of 75 years, Iannotti et al (1992) reported a mean glenoid height of 39 mm, a mean upper glenoid width of 23 mm and a mean lower glenoid width of 29 mm, consistent with our findings. If we compare our results with the Japanese and French samples of Mizuno et al (2017), our glenoid width is larger than the Japanese cohort, but smaller than the French, so we must consider ethnic differences in this type of measurement. However, the glenoid height is greater in both cases, so the glenoid of the Chilean population is more elongated.…”
Section: Discussionmentioning
confidence: 89%
“…In an evaluation of 140 shoulders of patients who were a mean age of 75 years, Iannotti et al (1992) reported a mean glenoid height of 39 mm, a mean upper glenoid width of 23 mm and a mean lower glenoid width of 29 mm, consistent with our findings. If we compare our results with the Japanese and French samples of Mizuno et al (2017), our glenoid width is larger than the Japanese cohort, but smaller than the French, so we must consider ethnic differences in this type of measurement. However, the glenoid height is greater in both cases, so the glenoid of the Chilean population is more elongated.…”
Section: Discussionmentioning
confidence: 89%
“…Recent literature on the glenoid version is almost completely focused on how to regain the version that guarantees joint stability during arthroplasty in patients with glenohumeral arthropathy and glenoid bone deficits. 1418 It has been confined to saying that there is a large individual variability in the glenoid version, 1922 which is commonly defined as the most variable parameter of the shoulder joint. Our doubt was: are intrinsic genetic factors or influences from extrinsic sources responsible for this variability?…”
Section: Discussionmentioning
confidence: 99%
“…Mizuno et al. 21 and Piponov et al. 22 found that the glenoid version differs in various ethnicities and genders.…”
Section: Discussionmentioning
confidence: 99%
“…Glenoid inclination was the angle between the anatomical axis and the axial anatomical plane ( Fig. 4B ) [ 2 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have indicated that measurement using three-dimensional (3D)-reconstructed bone models (3D measurement) for glenoid version and inclination is more accurate than 2D measurement [ 4 , 7 , 8 ]. More advanced analysis using software allows analysis of the scapula regardless of orientation [ 9 ]. Therefore, this study was performed to compare glenoid version and inclination in 2D and 3D measurements.…”
Section: Introductionmentioning
confidence: 99%